Proceso de atención de enfermería en paciente de 59 años de edad intervenida por uretropexia. - Rojas Rivera, Maidy Nayely (2023)
Genital prolapse affects countless patients, affecting the social, sexual, family and professional environment in which the woman develops, affecting the quality of life. This clinical case covers the study of the clinical manifestations, development and treatment of this pathology in a 59-year-old female patient. In any family environment, the fact that one of the members suffers from an illness and requires more attention is a determining factor, a situation that can cause discomfort and vital alterations. In general, stress incontinence can be treated with various conservative treatments. These include lifestyle changes, exercise, weight loss, or the insertion of bladder support devices. The present study deals with the case of a 59-year-old patient admitted through the outpatient area of the Martin Icaza Hospital, with a history of stress urinary incontinence, who attends her appointment with the Urologist who is admitted for surgery. The purpose of this practical case is to broaden knowledge in taking into account the symptoms that occur in the patient, checking the signs and symptoms and modified diagrams in order to apply a nursing process with appropriate interventions. Although surgery carries a higher risk of complications than other therapies, it can offer a long term. Finding the most appropriate surgical treatment for incontinence will depend on the risks and benefits of each procedure, as well as your specific health treatment needs.